The behavioural study of the bush dog (Speothos venaticus) in captivity with environmental enrichment - Carvalho, Thatijanne Santos Gonzaga de (2017)
The bush dog (Speothos venaticus) is very rare animal species, whose maintenance and breeding in captivity can induce the expression of atypical behaviour. Information concerning environmental enrichment and assessment models of the behaviour of this species in the literature are insufficient. Therefore, a study was conducted in the Zoo-Botanic Foundation of Belo Horizonte, Minas Gerais, Brazil, to evaluate the behaviour of two male bush dogs kept in captivity with different types of environmental enrichment, in April-May 2012. Data collection was performed before, during and after the presence of the environmental enrichment, three times a week in the morning and afternoon on alternate days for ten minutes, with immediate recording of activity performed by the animal every minute. It was observed that the animals interacted with all three types of ENRI used, but showed a greater interest in ENRI-2. No stereotyped behaviour or aggressive behaviour was observed, suggesting satisfactory welfare conditions for the animals in all environments tested. We conclude that the enrichment protocols can be used to stimulate the natural behaviour of the species, aiding the well-being and quality of life in captivity.